Financial Ratio Analysis For Predicting Financial Distress - Kinanti, Veronica Sonia; Muhyarsyah, Muhyarsyah (Green Publisher Indonesia, 2023)
This empirical study aims to analyze the financial ratios that can predict financial distress in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The study employs a quantitative approach with multiple linear regression analysis using eviews software. The data used in this study are secondary data obtained from the annual financial reports of the companies listed on the IDX. The study analyzes the potential for financial distress in the property and real estate sector and identifies the financial ratios that can predict financial distress. The results can provide insights for investors, regulators, and policymakers in identifying the potential for financial distress in the property and real estate sector. The study can also help companies in the sector to improve their financial performance and avoid financial distress. The study contributes to the existing literature on financial distress prediction models and provides empirical evidence on the effectiveness of financial ratios in predicting financial distress in the property and real estate sector.